Dança e cultura de massa: as contribuições do K-Pop para o processo ensino-aprendizagem em dança em Belém-PA - LEAL, Jaqueline Vasconcelos (2024)
This research aims to analyze and present the contributions brought by K-pop to the teaching learning process in dance in Belém-PA. Bibliographic research was carried out based on the studies of Rudolf Laban (1978), Lenira Rengel (2003; 2004; 2017), Ciane Fernandes (2006) and Bruna de Oliveira (2022), main theorists of this research, and a field research applied in K pop class of the Studio de Danças por Lucinha Azeredo, in Belém-PA, during the period from September to November 2023. The data obtained come from the bibliographic studies and testimonies of the students of the aforementioned class during the research. As a result, it has been found that K-pop in dance classes matures body control and awareness, expands the possibilities of movement, promoting the mastery and refinement of dance techniques and their applicability. It also stimulates the understanding of the proposal and impact of choreographies, also encouraging dynamism in it’s assembly and execution, as well as the identification and understanding of the tempo and time signature of the music, offering possibilities for experimentation and alternations in the original choreography proposal and modality.